Synthesis, characterization and biodegradability studies of nanocrystalline cellulose (NC) from banana stem (BS) reinforced poly lactic acid (PLA) biocomposite - Siti Norbaya Kasa (School of Materials Engineering, 2018)
The objectives of this study are to synthesize NC from banana stem through acid hydrolysis process and to modify NC surface polarity by acetylation reaction; to examine the tensile, thermal and morphological properties of synthesized and acetylated NC reinforced PLA biocomposites using an established characterization method; to investigate the biodegradability properties of synthesized and acetylated NC reinforced PLA biocomposites through the soil burial test.